(3JYHjQ GdQDjGs
(3ChdgG (B:s
(3fbd Yf HYV GdKbGJ CfNhGQRe TGg LeY ef cGf JMJ bHVJg ef GdYdeGA s
(3BNQgG (B:s
(3JOd Ydi GdfUQ hWjH GdbdH s
(3Vef eLehY s
(3hgj ebOeI eQJHg Ydi GdMQha GdCHLOjI YedJ ddedc eMeO Hf NhGQRe TGgs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B91 s
Keywords: (3JYHjQ GdQDjGs